3D reconstruction of nanocrystalline particles from a single projection. (January 2015) - Chen, F.-R.; Kisielowski, C.; Van Dyck, D.
Highlights: We present a new reconstruction scheme for 3D shape of nano particles at atomic resolution. The new approach only needs one projection direction. One can avoid the complicated tilting schemes and reduce the total electron dose. Abstract: This paper describes an approach to retrieve the three-dimensional atomic structure of a nanocrystalline particle from the reconstructed electron exit wave function in a single projection direction. The method employs wave propagation to determine the local exit surface of each atomic column together with its mass. The exit wave in between colums is used as internal calibration so as to remove the background noise and improve the precision to the level of single atom sensitivity. The validity of the approach is tested with exit wave functions of a gold wedge reconstructed from simulated images containing different levels of noise.